2012
DOI: 10.1001/jama.2012.6936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxychloroquine on Immune Activation and Disease Progression Among HIV-Infected Patients Not Receiving Antiretroviral Therapy

Abstract: Context Therapies to decrease immune activation might be of benefit in slowing HIV disease progression. Objective To determine whether hydroxychloroquine decreases immune activation and slows CD4 cell decline. Design, Setting, and Patients Randomized, double-blind, placebo-controlled trial performed at 10 HIV outpatient clinics in the United Kingdom between June 2008 and February 2011. The 83 patients enrolled had asymptomatic HIV infection, were not taking antiretroviral therapy, and had CD4 cell counts g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
148
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(153 citation statements)
references
References 31 publications
3
148
1
1
Order By: Relevance
“…34 Similar increases in plasma HIV levels had been seen in earlier studies of immunosuppressive agents: cyclosporine A, 35 prednisone, 36 and thalidomide 37 in untreated HIV infection. The mechanism whereby chloroquine enhances HIV replication is unclear.…”
Section: Figsupporting
confidence: 65%
“…34 Similar increases in plasma HIV levels had been seen in earlier studies of immunosuppressive agents: cyclosporine A, 35 prednisone, 36 and thalidomide 37 in untreated HIV infection. The mechanism whereby chloroquine enhances HIV replication is unclear.…”
Section: Figsupporting
confidence: 65%
“…In some studies this molecule was shown to reduce immune activation markers (i.e., IL-6, TNF-a and LPS) and CD8 T-cells expressing CD38CHLA-DRC and Ki-67, 158-161 while other researchers found no effect on immune-activation. [162][163][164] A possible target is also represented by TNF itself, which may be antagonized by several molecules currently in use for rheumatologic diseases. A study in rhesus macaques showed that adalimumab, a human anti-TNF monoclonal antibody, was able to reduce infiltration of polymorphonuclear cells into the T-cell zone of lymphoid tissues, diminishing also lymphoid tissue fibrosis; nevertheless, no effect on plasma immune activation was proven.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…Surprisingly, HCQ treatment in ART-naive nonprogressors resulted in a worsening of CD4 + T cell loss. 26 A NIAID-sponsored Phase II clinical trial is currently ongoing to determine whether treatment of HIV-infected patients would reduce HIV-induced immune activation (NCT00819390).…”
mentioning
confidence: 99%